"It's Both What You Say and How You Say It": Transgressive Language Practices Via Spoken Word Poetry. Issue 4 (2nd October 2017) - Desai, Shiv R.
Abstract : Marginalized youth of color manifest their imaginative and innovative utilization of language in a variety of ways. One area that has been understudied is how transgressive language practices allow youth to subvert and resist oppression. While these language practices are viewed as vulgar and inappropriate for school, for disenfranchised youth they are aligned with identity and agency. The author's purpose is to highlight the creativity employed by alienated who engage in transgressive language practices within their spoken word poetry and how it can be leveraged as a pedagogical resource.